Augmented Reality-Based Medical Equipment Learning Application - Nur Annisa Hasanuddin; Wafiah, Andi; Hasnawati (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
The rapid development of information technology offers significant opportunities for innovation in learning media, particularly in the healthcare field. One technology that can be utilized is Augmented Reality (AR), which allows users to directly interact with virtual objects in three-dimensional form. This study aims to design and develop an AR-based medical equipment learning application to help students recognize and understand medical instruments more effectively and interactively. The application was developed using Unity and Blender to create 3D object visualizations and was tested using black box and white box testing methods to ensure system reliability. The test results show that the application runs well and is positively received by users, as it can display interactive 3D models of medical equipment, provide descriptions, and offer evaluation quizzes. Therefore, this application has the potential to serve as an innovative supplementary learning medium, addressing the limitations of laboratory equipment and enhancing students’ understanding of medical instruments.